One-year Evaluation of Team-based Care in Primary Healthcare in Saudi Arabia: Achievements, Barriers, and Challenges - Nada Abdulghani Sarooji,; Abeer Maula Alahmadi,; Hanan Fawaz Sabban,; Zainab Saeed Algarni,; Hanaa Ahmed Ali Asiry,; Rehab Abdullah Almourey,; Tahani Saleh Alghamdi,; Sahar Mohammed Ali Alfadeel,; Asmahan Nasir Ali balobaid, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction:Evidence shows that in most developed countries, PHC has gradually transformed into team-based care, where health professionals work to the top of their skills and can interact within a team or across teams, coordinating and integrating services, resulting in better health care delivery. Aim: Assess the team based care in the primary healthcare in Saudi Arabia from patients prospectives. Method: descriptive cross sectional research design was utilized. Settings: It was conducted in four primary healthcare (PHCs) at JEDDAH city, Saudi Arabia, during August-December 2024. This PHCs were selected using stratified random sampling from 95 PHCs in Jeddah. Sampling : Stratified random sampling was utilized to select proposed sample 425 patent were assigned to participate in the questionnaire Tools: one tool was utilized to assess patients prospectives satisfaction toward team-based care. Results: this study reveals that that they perceived high level of satisfaction70.184 with mean SD (87.73± 29.34) regarding team based are . In addition, they perceived high level related to Overall satisfaction of service, Early screening, Health education and follow up, Beneficiary satisfaction of service, Easy Accessibility, and communication, ( 66.4%,70.00%,66.8%,73%68.3%, and 72.3% )respectively . The Beneficiary satisfaction of service was the highest dimension (72.3%) while over all perception regarding service were the lowest one( 66.4%). In addition, more than 50% had able to use SehattyApplication. Furthermore, 54.5 % had no difficulty when getting an appointment while using sehatty application. they recommended to enhance the appointment service to decrease waiting time in the clinics , although the three quarter had no recommendation. Conclusion: team-based care is an important service in the primary healthcare and patients who utilized this service were satisfied.ssessing patients' perspectives on TBC using the PHC system is the aim of this study. Our research indicates that patients were generally satisfied with their service. The type of the services provided and patient characteristics were shown to be two of the many factors that contribute to satisfaction. Implications: develop a strategy to enhance appointment services in the team-based care.